PIBID e formação do professor de história na Urca (2009-2014) - Rolim, Márcia Justino (2016)
The college degrees have been gaining a challenging character nowadays when it comes to the processes of formation of teachers. Recently, those processes gained a significant contribution and it is called Programa Institucional de Bolsa de Iniciação à Docência (PIBID) funded by the Coordenação de Aperfeiçoamento Pessoal de Nível Superior (CAPES) with the aiming of developing actions attributed in the politics of formation of future teachers that will develop their teaching skills on the Basic Education. As a challenging process, we aim to recognize and get to know the contributions and the impacts that PIBID brought on the Cariri’s Regional University (URCA), localized in the city of Crato/CE, South of Cariri, inside the History degree in the years of 2009-2014. To analyze our studies, we opted for a quantitative approach when it comes about our data through answer sheets applied, two interviews and discussions about the teaching formation of the History professional in the process of teaching inside the program PIBID. Contributed to this work, forty students included in the program (PIBID), five supervisor teachers of public schools linked to the program and the university, and two coordinators of the History course. We hope that this is one more contribution for future teachers of the basic education to develop their job as an enriching process for the degrees nowadays. We expect that this job is recognized as one more study of case, inside the program of professional formation. We also hope that other works have the same purpose or at least approximate the worries in the academic formation in our institutional ambiances.